2022
DOI: 10.1097/hjh.0000000000003213
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and severe acute respiratory syndrome coronavirus 2 infection: a systematic review

Abstract: Objective:Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of the coronavirus disease 2019 (COVID-19) disease that has rapidly spread worldwide, causing hundreds of thousand deaths. Normal placentation is characterized by many processes strictly regulated during pregnancy. If placentation is impaired, it can lead to gestational disorders, such as preeclampsia that is a multisystem disorder that occurs in 2–8% of pregnancies worldwide.Methods:We performed a systematic search to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 84 publications
0
37
0
Order By: Relevance
“…Last but not least, SARS-CoV-2 infection not only causes damage to the respiratory tract but can affect other organs. Emerging studies have connected COVID-19 with the onset of preeclampsia during pregnancy [47], problems of the reproductive system in men (i.e., deterioration in semen parameters) [48] and neurological complications [49]. Hence, future studies are needed in order to better understand the virus-host-microbiome interplay so that improved therapeutic approaches can be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, SARS-CoV-2 infection not only causes damage to the respiratory tract but can affect other organs. Emerging studies have connected COVID-19 with the onset of preeclampsia during pregnancy [47], problems of the reproductive system in men (i.e., deterioration in semen parameters) [48] and neurological complications [49]. Hence, future studies are needed in order to better understand the virus-host-microbiome interplay so that improved therapeutic approaches can be developed.…”
Section: Discussionmentioning
confidence: 99%
“…This should be done to definitively identify if coagulopathic or inflammatory pathologies are increased in this population. The fact that 84% of patients were asymptomatic was another important limitation of our study; a recent systematic review showed that the severity of the infection plays a key role in pregnancy outcome [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases, it can cause pneumonia, acute respiratory distress syndrome, sepsis, septic shock and a cytokine storm with multiorgan failure and disseminated coagulopathy, leading to death [ 6 ]. Furthermore, SARS-CoV-2 infection can cause non-respiratory complications—brain haemorrhage, memory loss, altered mental states in both sexes, semen quality worsening in male patients [ 7 , 8 ] and pregnancy complications such as preeclampsia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vascular complications, myocardial dysfunction, acute kidney injury, gastrointestinal symptoms, neurologic complications, and dermatologic conditions are among the reported extrapulmonary complications [ 2 , 3 ]. Furthermore, recent studies have suggested that COVID-19 could also have a serious impact on the reproductive system, altering male sperm parameters and increasing the rate of female gestational disorders, such as preeclampsia [ 4 , 5 ]. However, whether COVID-19 could also directly affect the liver has been debated, and the literature regarding hepatic involvement in COVID-19 patients is heterogenous, due to variability in the definitions of liver dysfunction and differences in the clinical presentation and disease severity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%